COMMUNICATIVE SPACE OF DISTANCE LEARNING FOR UNIVERSITY STUDENTS - A. P. Avdeeva; Yu. A. Safonova (Вестник университета)
The article considers the actual problem of organizing the communication space of distance learning for first-year students of the university. The development of information technologies, the need to introduce innovative approaches, the emergence of global extreme social situations, such as the COVID-19 pandemic of 2019–2021years, – intensified the use of distance approach in educational activities. The purpose of this article is to study the experience of organizing the communicative space of distance learning, because communicative space is one of the key factors for effective learning. As a result of the empirical research, the issues of the formation of the communicative process, social connections and attitudes to educational activities among first-year students have been analysed. The paper concludes, that the effectiveness of the organization of the communicative space of distance learning depends largely on the communicative competencies of the teacher. The study reveals the most important  competencies of teachers for organizing the communication space of online learning – the focus on innovation, the development of empathic abilities of teachers, business and Internet-communication skills.